COVID-19 infection and extensive subdural empyema: cause or consequence? - Aldo Jose Ferreira da Silva; Daniel Fonseca Oliveira (Brazilian Society for Pediatric Neurosurgery, 2023)
Adolescent, female, 12 years old, with a history of headache and vomiting, without fever, with progressive worsening and coma. Laboratory tests showed positive SARS-CoV-2 PCR RNA. She has not had the vaccine for COVID-19. A non-contrast-enhanced cranial tomography(Figure 1a) showed a right fronto-temporo-parietal cortical hypodense area with significant midline shift. A decompressive craniectomy was performed with drainage of extensive subdural empyema(Figure 1c). Subdural empyema is most often a consequence of paranasal sinus infections. With the COVID-19 virus also located in the paranasal sinuses, it is not possible to determine whether it is a consequence or cause of subdural empyema (1). Although the pathophysiology is unclear, it is possible that upper respiratory infection by COVID-19 creates a favorable environment for bacterial sinusitis coinfection(Figure 1b), intracranial extension, and formation of subdural empyema (2). Another possible explanation is that the SARS-CoV-2 virus infection affects the immune system and makes the individual more susceptible to infection (3). Therefore, more studies are needed to clarify the relationship between SARS-CoV-2 infection and other infections.   Figure Caption Figure 1 (a) Computed tomography of the skull, with the axial section showing a right fronto-temporo-parietal hypodense area(black arrows) with significant midline shift(black arrowheads). (b) Computed tomography of the skull, with the coronal section showing signs of sinusitis with opacification of the right ethmoid sinus(black arrow). (c) Intraoperative view after opening the dura mater showing exposure of the right fronto-temporo-parietal cortex covered by viscous purulent secretion(black arrow). (d)  Computed tomography of the skull, with the coronal section showing after treatment without ethmoid opacification(black arrow) and small postoperative CSF collection(black arrowhead).